The novel SERPINC1 missense mutation c.1148 T > A (p.L383H) causes hereditary antithrombin deficiency and thromboembolism in a Chinese family: a case report - Fangkai He; Yang Wang; Weiwei Ning; Chao Liu; Xiaojun Guan; Yao Yao (Journal of Medical Case Reports)
Abstract Background Hereditary antithrombin deficiency, an autosomal-dominant thrombotic disease caused by a SERPINC1 gene deficiency, is extremely rare, although it is the leading cause of hereditary thrombophilias. Herein we report a novel SERPINC1 gene mutation in a Chinese family and one case of pulmonary embolism associated with the mutation. We also discuss the latest diagnostic and treatment strategies for antithrombin deficiency. Case presentation The 33-year-old Chinese male proband had a pulmonary embolism and there was no evidence of thromboembolism in the other family members. In the pulmonary embolism case, treatment with nadroparin calcium combined with warfarin failed; however, rivaroxaban was effective. No emboli were evident in the follow-up computed tomography pulmonary angiography. Antithrombin activity fluctuated approximately 50% during hospitalization and follow-up. The antithrombin activity of the proband, his 58-year-old father, and his 5-year-old son was significantly low (44–48%). A novel missense variant c.1148 T > A (p.L383H) in the SERPINC1 gene was identified in these three family members. The pathogenesis predictions from Mutation-Taster, Provean, and SIFT were “disease-causing,” “deleterious,” and “damaging,” respectively. Conclusion The novel c.1148 T > A (p.L383H) pathogenic mutation in the SERPINC1 gene updated the gene mutation spectrum of hereditary antithrombin deficiency. Direct oral anticoagulation with rivaroxaban may be a more effective and selective anticoagulant in patients with hereditary antithrombin deficiency over warfarin or heparin.